Spatial Assessment of Para Rubber (Hevea brasiliensis) above Ground Biomass Potentials in Songkhla Province, Southern Thailand - John Nyandansobi Simon; Narissara Nuthammachot; Teerawet Titseesang; Kingsley Ezechukwu Okpara; Kuaanan Techato (My University, 2021)
Currently, Songkhla Province of Thailand has been recognized as a convenient hub of rubber industry development, accompanied by an attendant abundance of rubber tree plantations. A spatialized assessment of the rubber tree was carried out to estimate its aboveground biomass potentials using remote sensing techniques and ecosystem modeling procedures. Moderate Resolution Imaging Spectroradiometer satellite-based estimations of the net primary productivity were derived and complemented with a calculated generic model, to quantify the respective above ground biomass potentials para rubber. Above ground biomass assessment findings revealed a mean value of 82.1 tonnes C ha−1 and an aggregate of 31. 9 million tonnes C ha−1 which is the theoretical potential, this is segregated into energy usable, and other economic purpose biomass potentials, with corresponding value ranges of 1624.1 to 6,041,531.2 million tonnes C ha−1 and 85.5 to 317,975.6 thousand tonnes C ha−1 respectively. Besides the theoretical above ground biomass potential (entire biomass accumulation ratio) commonly evaluated, the other potentials, which include naturally obtainable biomass usable for energy generation and the remaining share of the feedstock for non-energy uses, have been brought to light. Songkhla province has the potential for good carbon sink and sustainable supply of different pools of feedstock from the rubber tree that reinforces each other in providing a comprehensive view of biomass in energy and non-energy opportunities. The socioeconomic production and value chain analysis of the identified biomass pools needs to be evaluated; this will consequently guide policy toward a comprehensive rubber sector sustainable development.
Keywords: Tonne; Oil Palm Production and Sustainability